2017
DOI: 10.1038/ajg.2017.48
|View full text |Cite
|
Sign up to set email alerts
|

Constipation-Predominant Irritable Bowel Syndrome Females Have Normal Colonic Barrier and Secretory Function

Abstract: Objective To determine if constipation predominant IBS (IBS-C) is associated with changes in intestinal barrier and secretory function. Design 19 IBS-C patients and 18 healthy volunteers (all females) underwent saccharide excretion assay (0.1 g 13C mannitol and 1 g lactulose), measurements of duodenal and colonic mucosal barrier (transmucosal resistance (TMR), macromolecular and E. coli Bio-Particle translocation), mucosal secretion (basal and ACh evoked short circuit current, Isc), in vivo duodenal mucosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 36 publications
3
48
0
2
Order By: Relevance
“…Previous studies on I sc and IBS are mostly lacking, however, recently Peters et al 54 showed a similar I sc in IBS-C and HCs, which is in line with our findings and indicates an increased bacterial uptake in IBS, even in circumstances where ion transport is unchanged. To further determine changes in permeability due to tight junction components, we chose to study occludin and ZO-1 expression, as main constituents of the apical junctions, based on previous reports demonstrating its deregulation in the colon of IBS 13 Our study confirms previous data and extends its contribution to bacteria-mediated epithelial alterations.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies on I sc and IBS are mostly lacking, however, recently Peters et al 54 showed a similar I sc in IBS-C and HCs, which is in line with our findings and indicates an increased bacterial uptake in IBS, even in circumstances where ion transport is unchanged. To further determine changes in permeability due to tight junction components, we chose to study occludin and ZO-1 expression, as main constituents of the apical junctions, based on previous reports demonstrating its deregulation in the colon of IBS 13 Our study confirms previous data and extends its contribution to bacteria-mediated epithelial alterations.…”
Section: Discussionsupporting
confidence: 92%
“…Two techniques are available: first, confocal endomicroscopy, which shows leaks of intravenously administered fluorescein into the gut lumen during endoscopy49 (eg, in response to food-associated changes in the intestinal mucosa of patients with diarrhoea-predominant IBS); and second, endoscopic mucosal impedance, in which a 2 mm diameter catheter is passed through an endoscope and placed in contact with the duodenal mucosa under direct visualisation, and two circumferential sensors, placed 2 mm apart on the mucosa for 0.10 s, in the four quadrants of the duodenum with a decompressed lumen, and all fluid aspirated 50. The studies of food-associated changes during these challenge tests provide some evidence that there can be barrier changes that may indeed support the concept of transient ‘leakiness’ of the gut.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in small intestinal 93 and colonic secretion represents another pathophysiologic disturbance in FGIDs that may be influenced by the gut microbiome 48 ( Figure 3 ). Secretory mechanisms are common therapeutic targets 94, 95 of medications used to treat FGIDs.…”
Section: Effect Of the Gut Microbiota On Host Physiologymentioning
confidence: 99%